HOXD9 promotes epithelial–mesenchymal transition and cancer metastasis by ZEB1 regulation in hepatocellular carcinoma. Issue 1 (December 2015) - Lv, Xiupeng; Li, Linlin; Lv, Li; Qu, Xiaotong; Jin, Shi; Li, Kejun; Deng, Xiaoqin; Cheng, Lei; He, Hui; Dong, Lei
Abstract Hepatocellular carcinoma (HCC) is a common malignant tumor that severely threatens human health. The poor prognosis of HCC is mainly attributed to intrahepatic and extrahepatic metastases. HOXD9 proteins belong to a superfamily that regulates the development and control of many cellular processes, including proliferation, apoptosis, cell shape, and cell migration. HOXD9 can also function as an oncogene in several cancer cells. However, its biological function in human HCC requires further investigation. In this study, HOXD9 exhibited high expression in invasive HCC cells. HOXD9 overexpression can significantly enhance HCC cell migration, invasion, and metastasis, whereas silencing HOXD9 inhibits these processes. HOXD9 also promotes the epithelial–mesenchymal transition (EMT) of HCC cells. Microarray analysis suggests that ZEB1 can function as a downstream factor of HOXD9. HOXD9 can interact with the promoter region of ZEB1 and promotes ZEB1 expression. ZEB1 knockdown inhibits HOXD9-induced migration and invasion, as well as EMT in HCC cells. This study helps elucidates the oncogenic functions of HOXD9 in HCC.